PEMBELAJARAN SOAL CERITA HITUNG CAMPURAN MELALUI PENDEKATAN KONSTRUKTIVISME - Neni Nadiroti Muslihah (Al-Aulad: Journal of Islamic Primary Education, 2018)
Mathematical problems are generally closely related to daily life. The problem is very important given to elementary school students because in general the story can be used to train students in solving problems. Solving stories can be used as a problem-solving strategy, although the question of mathematics is not necessarily a problem-solving question. The ability needed to solve the story problem is not only skill ability and maybe certain algorithm but also other ability that is ability to make plan and strategy that will be used in reaching completion. In addition, learning about the mixed story can also train the learners in their learning ability related to the three aspects of cognitive, affective, and psychomotor. Therefore, the ability of teachers as educators either personal or professional should take precedence. However, in reality, the teaching-learning process that is implemented tends to passively, where the concepts obtained by learners are still centered on the teacher. So it is necessary to find an alternative learning that can improve student learning outcomes. The constructivism approach is one of the proper approaches used in mathematics learning about mixed counts. Because, according to the expert view of constructivism, every learner has a role in determining what is learned. Emphasis is given to learners in order to form skills and knowledge by linking past experience with future use. Learners are not only given emphasis on facts or concepts but also given emphasis on the process of thinking and communication skills.